2001
DOI: 10.1136/ard.60.2.133
|View full text |Cite
|
Sign up to set email alerts
|

Increased peripheral T cell reactivity to microbial antigens and collagen type II in rheumatoid arthritis after treatment with soluble TNFα receptors

Abstract: Objective-Peripheral T cells from patients with rheumatoid arthritis (RA) are hyporesponsive when stimulated with antigen or mitogen in vitro, possibly owing to increased production of proinflammatory cytokines such as tumour necrosis factor (TNF ). This study sought to find out if and how RA T cell reactivity is aVected during treatment with etanercept (Enbrel), a soluble TNF receptor. Methods-Heparinised blood was collected from patients with RA at baseline, after four and eight weeks of etanercept treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
50
2
4

Year Published

2002
2002
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 35 publications
4
50
2
4
Order By: Relevance
“…Instead, many of them had an untreated, longstanding, active and destructive RA disease associated with a persistent stimulation of the immune system rather than with a state of immunosuppression. An interesting possible explanation, and one that supports the notion of a role for inflammatory activity in the development of lymphomas, was found in a study by Wahl et al (40) and subsequently confirmed by many groups, including our own (41). In these studies, it has been shown that apart from being associated with a stimulation of certain immune functions, RA may also cause suppression of other functions.…”
Section: Discussionsupporting
confidence: 81%
“…Instead, many of them had an untreated, longstanding, active and destructive RA disease associated with a persistent stimulation of the immune system rather than with a state of immunosuppression. An interesting possible explanation, and one that supports the notion of a role for inflammatory activity in the development of lymphomas, was found in a study by Wahl et al (40) and subsequently confirmed by many groups, including our own (41). In these studies, it has been shown that apart from being associated with a stimulation of certain immune functions, RA may also cause suppression of other functions.…”
Section: Discussionsupporting
confidence: 81%
“…Overall, our study thus lends strong support to the recent emerging conviction that TNF-␣ is a double-edged sword, and besides its proinflammatory properties, it plays an important immunoregulatory function in the host response to a number of intracellular infections and autoimmunogens. 21,22,[32][33][34][35][36][37][38][39][40] In our current study, we have found TNF-␣ regulation of MCP-1 responses to be an important molecular mechanism by which TNF-␣ negatively controls the level of influenza immunopathology. MCP-1 has previously been reported to be a major profibrotic chemokine involved in various fibrotic processes, including recruitment of fibrocytes, induction of collagen synthesis, and up-regulation of TGF-␤1 expression in various models.…”
Section: Discussionmentioning
confidence: 93%
“…[3][4][5][6][7][8][9][10][11] TNF-␣, a classical proinflammatory cytokine, has recently been shown to play anti-inflammatory and antifibrotic roles in various models. [32][33][34][35][36][37][38][39][40][41][42][43] However, whether TNF-␣ plays an immunoregulatory role during influenza infection remains unclear. Using a mouse model of respiratory influenza infection, we investigated this issue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immun-mekanizma sebepli tablolar›n ortaya ç›kmas›, TNF'in yok edilmesi s›ras›nda artm›fl T ve B hücre aktivasyonunun, otoantijenler ve yabanc› antijenler ile reaksiyonlar›na ba¤lanm›flt›r. [125][126][127][128] TNF antagonistleri ile tedavi sonras›nda baflta anti-nukleer antikor ve antidsDNA antikor olmak üzere çeflitli otoantikorlar›n artt›¤› bilinmektedir. 129,130 Bu konuda yap›lan bir araflt›rmada 7700 infliksimab ve 3800 etanersept kullanan hasta grubunda lupus-benzeri tablo geliflen olgu say›s› yaln›z 22 (15 infliksimab ve 7 etanersept) olarak bildirilmifltir.…”
Section: Tnf Antagonistleriunclassified